Optimizing the Care and Health of Women with Inflammatory Bowel Disease - Judy Nee; Joseph D. Feuerstein (Gastroenterology Research and Practice)
Inflammatory bowel disease (IBD) including both ulcerative colitis and Crohn’s disease is increasing worldwide. Although diagnosis is equally found in men and women, the chronicity of IBD poses a unique impact on the milestones of a woman’s life. As the gastroenterologist becomes increasingly important in the health maintenance of patients with IBD, this review stresses the unique gender issues in women with IBD related to menstruation, cervical cancer, sexual health, contraception, and menopause that may affect the course of disease, treatment decisions, and quality of life.